2021
DOI: 10.1007/s12350-019-01946-y
|View full text |Cite
|
Sign up to set email alerts
|

Cell proliferation detected using [18F]FLT PET/CT as an early marker of abdominal aortic aneurysm

Abstract: Background. Abdominal aortic aneurysm (AAA) is a focal aortic dilatation progressing towards rupture. Non-invasive AAA-associated cell proliferation biomarkers are not yet established. We investigated the feasibility of the cell proliferation radiotracer, fluorine-18fluorothymidine ([ 18 F]FLT) with positron emission tomography/computed tomography (PET/ CT) in a progressive pre-clinical AAA model (angiotensin II, AngII infusion).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 38 publications
0
18
0
1
Order By: Relevance
“…The suprarenal aortic volume was calculated in mm 3 (over the monitored distance of 12 mm) with Vevo Lab 3.1.1 software; images of ECG-gated kilohertz visualization were used to additionally determine the maximum diameter of the aorta (inner-to-inner wall) at maximal blood flow. 19 Independent measurements by 3 observers were averaged in volume and diameter calculations.…”
Section: Methodsmentioning
confidence: 99%
“…The suprarenal aortic volume was calculated in mm 3 (over the monitored distance of 12 mm) with Vevo Lab 3.1.1 software; images of ECG-gated kilohertz visualization were used to additionally determine the maximum diameter of the aorta (inner-to-inner wall) at maximal blood flow. 19 Independent measurements by 3 observers were averaged in volume and diameter calculations.…”
Section: Methodsmentioning
confidence: 99%
“…18 Using the angiotensin II-induced AAA murine model, Gandhi et al showed that there is increased [ 18 F]fluorothymidine ([ 18 F]FLT) uptake on day 14 post-aneurysm induction, but this uptake is significantly reduced on day 28. 19 These findings have important implications in supporting the idea of early-stage cellular remodeling that may drive disease progression, a notion that has been introduced and deliberated by several groups. [20][21][22] In the future, knowledge gained from these studies may facilitate early-stage risk stratification; however, further preclinical and clinical investigations are warranted to reinforce this theory.…”
Section: Preclinical Studiesmentioning
confidence: 83%
“…This study provides the first proof-of-concept data for PET-CT as a potential imaging assessment for AAA risk-stratification. A recent pre-clinical study using the AngII-infusion AAA model reported that the uptake of the cell proliferation radiotracer, Fluorine-18-fluorothymidine ((18F)FLT) is increased during the active growth phase of the AAA [ 102 ]. Addition of such novel radiotracer agents to PET-CT could enhance the ability to identify which AAAs require surgical repair.…”
Section: Use Of New Imaging Methods To Study Aaa Rupturementioning
confidence: 99%